2019
DOI: 10.1177/0885328219866039
|View full text |Cite
|
Sign up to set email alerts
|

Chemical and thermal deproteinization of human demineralized tooth matrix: Physicochemical characterization and osteoblast cell biocompatibility

Abstract: Although human tooth was developed for using as a bone graft material due to their similarity in chemical composition compared to human bone, the clinical application was limited to autologous use. The aims of this study were to develop the deproteinized human demineralized tooth matrix to be used as a bone graft substitution. The physicochemical characteristic and osteoblastic cell biocompatibility of these materials were analyzed and compared. Human demineralized tooth matrix was prepared by using 0.5 M HCl.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 43 publications
0
17
0
Order By: Relevance
“…In a recent in vitro study conducted by Tanwatana et al, 14 several processes, such as thermal and chemical deproteinization of tooth matrix, demonstrated favorable proliferation and attachment of osteoblasts. They concluded that the demineralized and deproteinized tooth matrix is a suitable scaffold for osteoblasts.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent in vitro study conducted by Tanwatana et al, 14 several processes, such as thermal and chemical deproteinization of tooth matrix, demonstrated favorable proliferation and attachment of osteoblasts. They concluded that the demineralized and deproteinized tooth matrix is a suitable scaffold for osteoblasts.…”
Section: Discussionmentioning
confidence: 99%
“…The evaluation of annealed toothpowder's direct and indirect cytotoxicity did not show a cytotoxic effect on human alveolar bone marrow stem cells. 41 MC3T3-E1 osteoblasts cell line adheres and proliferates to the surface of chemical (sodium hydroxide) and thermal-treated tooth powder, forming a multilayered and dense cell sheet accumulated after 7 days of culture. 41 Several researchers claimed that deproteinisation of tooth-derived materials decreases immunogenicity and prevents the host's immune following implantation.…”
Section: Objectivesmentioning
confidence: 99%
“…41 MC3T3-E1 osteoblasts cell line adheres and proliferates to the surface of chemical (sodium hydroxide) and thermal-treated tooth powder, forming a multilayered and dense cell sheet accumulated after 7 days of culture. 41 Several researchers claimed that deproteinisation of tooth-derived materials decreases immunogenicity and prevents the host's immune following implantation. However, to the best of our knowledge, any in vitro evaluation of the inflammatory and immune cell response to deproteinized GBM or BBM was found in the literature.…”
Section: Objectivesmentioning
confidence: 99%
“…The chemical composition of bone and dentin are quite similar including hydroxyapatite (Hap) and type I collagen showing a high degree of cross-linking with matrix-binding proteins and growth factors such as IGF-II, BMP-2, and TGF [40,41]. Dentin-derived matrix granules are prepared from teeth which have been extracted due to trauma, advanced periodontal bone loss, or other indications such as wisdom teeth or orthodontic treatment.…”
Section: Chemical Composition and Morphological Aspects Of Dentin-der...mentioning
confidence: 99%
“…In fact, several protocols for the preparation of ATDM granules have been reported in the literature. Therefore, several other terms have been applied for ATDM depending on the processing protocols such as demineralized dentin-matrix (DDM), deproteinized demineralized dentin-matrix (dDDM), tooth-derived dentin-matrix (TDM), mineralized dentin-matrix (MDM), or partially mineralized dentin-matrix (PDM) [37,40,47].…”
Section: Chemical Composition and Morphological Aspects Of Dentin-der...mentioning
confidence: 99%